Low-Level Laser Irradiation Modulated Viability of Normal and Tumor Human Lymphocytes In Vitro - Saghaei Bagheri, Hesam; Rasta, Seyed Hossein; Mohammadi, Seyedeh Momeneh; Rahimi, Ali Akbar Rahim; Movassaghpour, AliAkbar; Nozad Charoudeh, Hojjatollah (Journal of Lasers in Medical Sciences, 2020)
Introduction: Laser radiation is a promising strategy against various malignancies. Recent studies have shown that the application of low-power laser therapy (LPLT) at different doses and exposure times could modulate the growth dynamic of tumor cells. Based on the type of laser, LPLT could potentially trigger cell proliferation, differentiation, and apoptosis in different cell lines. Methods: In this study, MTT assay was used to monitor the effect of low and high laser intensities on the viability of normal and cancer lymphocytes. The protein levels of Ki-67 (a proliferation marker) and Caspase-3 (an apoptosis factor) were measured in human peripheral mononuclear cells (PBMCs) and the B-lymphoblastic cell line (Nalm-6) using flow cytometry after being-exposed to 630-nm LPLT at low (2, 4, 6, and 10 J/cm2) and high (15, 30, 60, and 120 J/cm2) energy densities in a continuous mode for 48 and 72 hours. Results: By using higher energy densities, 60 and 120 J/cm2, a significant decrease was shown in the viability of Nalm-6 cells, which reached 6.6 and 10.1% after 48 hours compared to the control cells (P < 0.05). Notably, Cell exposure to doses 30, 60, and 120 J/cm2 yielded 7.5, 12.9, and 21.6 cell viability reduction after 72 hours. The collected data showed that the high-intensity parameters of LPLT (15 to 120 J/cm2) promoted significant apoptotic changes in the exposed cells coincided with the activation of Caspase-3 compared to the none-treated control cells (P < 0.05). The data further showed the stimulation of the Ki-67 factor both in primary PBMCs and the lymphoblastic cell line treated with LPLT at energy densities of 4 and 6 J/cm2 (P < 0.05), indicating enhanced cell proliferation. Similar to Nalm-6 cells, primary PBMCs showed apoptosis after 48 hours of being exposed to doses 60, and 120 J/cm2, indicated by increased Caspase-3 levels (P < 0.05). As expected, the Nalm-6 cells were resistant to cytotoxic effects of laser irradiation in the first 48 hours (P > 0.05) compared to normal PBMCs. The exposure of Nalm-6 cells to low-intensity laser intensities increased a proliferation rate compared to the PBMCs treated with the same doses. Conclusion: We showed the potency of LPLT in the induction of apoptosis and proliferation in human primary PBMCs and Nalm-6 cells in a dose and time-dependent manner after 72 hours.